Contract documents for landscaping work with all necessary items, plants for Brac University new campus building at holding no. Kha 224, Merul Badda, Dhaka.-1212 - Brac University (Brac University, 2023)
This agreement made between Brac University and BRAC Nursery Enterprise for landscaping work with all necessary items, plants for Brac University new campus project.